The Effect of Blended Learning Approach Using Teachmint Application on Students' Learning Outcomes and Digital Literacy on Buying and Selling Activities in Grade 4 Elementary School - Rahayu, Sukemining; Yuliati, Nanik; Wuryaningrum, Rusdhianti (MSJ : Majority Science Journal, 2025)
The purpose of this study is to investigate the impact of the Teachmint application and the Blended Learning approach on the academic performance and digital literacy of fourth-grade elementary students concerning buying and selling-related topics. This research employs a quasi-experimental framework and an experimental design featuring a pretest-posttest control group. The focus of this study is on forty fourth-grade primary school students. Proportional random sampling was utilized for selection in this research. Data for this study was collected through a test. A t-test was the statistical method utilized to examine the data with SPSS version 26. Given that the significance value of 0. 000 is lower than the established significance threshold of 0. 05, the results of the t-test suggest that blended learning via the Teachmint application has a substantial effect on student performance. The results of the independent sample t-test also indicate that there is a significant enhancement in students' digital literacy when blended learning strategies are implemented. This conclusion is further corroborated by the t-test results, which show a value of 0. 042